Acetabular Configuration and its Impact on Cup Coverage of a Subtype of Crowe Type 4 DDH with Bi-Pseudoacetabulum. Issue 2 (March 2013) - Yi, Chengqing; Ma, Chunhui; Wang, Qian; Zhang, Guoqiao; Cao, Yun
The purpose of this study was to explore the acetabular configuration of a special subtype of Crowe type 4 DDH and its impact on cup coverage, which was identified with a particular bi-pseudoacetabulum and an inter-pseudoacetabulum spine structure. The altered bone stock and anatomic structures were believed to be a result of lesser trochanter impingement on the pelvis as observed in all hips of this series, which was supported by the radiographic and intraoperative findings. Acetabular characteristics were depicted by means of radiographic assessment and direct observation during surgery. Pre-Operatively, the horizontal distance to the hip centre was 80.5 mm on average and 52.9 mm for femoral head height with a significant difference compared to the general series of DDH cases. Anterosuperior bony coverage was found to be more adequate with a thicker anterior wall. The postoperative hip centre was restored to the true acetabulum to within 23.4 mm vertically and 25.2 mm horizontally, and sufficient cup containment was achieved when the acetabular inclination angle was below 45°. A larger diameter cup (range 46-50 mm) was employed. No structural bone graft was required, and the medial protrusion technique was infrequently required. This subtype of DDH facilitated cup coverage during THA.